The Effect of Microsoft Office PowerPoint on Students’ Writing Competence at SMPN 9 Kendari - Rahmawati, Ima; Nurnia, Nurnia; Muhsin, Muh. Khusnun (Universitas Halu Oleo, 2021)
This research aims at investigating the effect of Microsoft office PowerPoint on student competence in writing descriptive text. The design of this research was descriptive quantitative research. This research used a pre-experimental with One-Group Pretest-Posttest design (class VIII). The total sample was 30 students which were selected by using the probability sampling technique. The instrument of this research was a writing test that focused on two aspects of writing namely vocabulary and language use. The researcher collected the data by giving pre-test and post-test to know students writing competence before and after treatment of Microsoft office PowerPoint had been applied. The researcher used Microsoft excel 2010 and SPSS 16.0 to analyze the result of this research. The finding showed that there was an effect of Microsoft office PowerPoint on students' writing competence. The result of the descriptive analysis showed the mean score of pre-test was 51.76 and the mean score of post-test was 79.70. The inferential statistics showed that there was a significant effect of Microsoft Office PowerPoint on students' writing competence. Hence, teaching and learning writing use Microsoft office PowerPoint can be one of the effective methods for upgrading students‟ writing competence